A Decoupling Analysis of the Crop Water Footprint Versus Economic Growth in Beijing, China - Huang, Kai; Wang, Mengqi; Zhou, Zhongren; Yu, Yajuan; Bi, Yixing (Frontiers in Environmental Science, 2021)
Beijing, the capital of China, is experiencing a serious lack of water, which is becoming a main factor in the restriction of the development of the social economy. Due to the low economic efficiency and high consumption proportion of agricultural water use, the relationship between economic growth and agricultural water use is worth investigating. The "decoupling" index is becoming increasingly popular for identifying the degree of non-synchronous variation between resource consumption and economic growth. This paper involves the water footprint (WF) to assess the water consumption in the crop production process. After an evaluation of the crop WF in Beijing, this paper applies the decoupling indicators to examine the occurrence of non-synchronous variation between the agricultural gross domestic product (GDP) and crop WF in Beijing from 1981 to 2013. The results show that the WF of crop production in 2013 reduced by 62.1% compared to that in 1980 — in total, 1.81×109 m3. According to the decoupling states, the entire study period is divided into three periods. From 1981 to 2013, the decoupling states represented seventy-five percent of the years from 1981 to 1992 (Period I) with a moderate decoupling degree, more than ninety percent from 1993 to 2003 (Period II) with a very strong decoupling degree and moved from non-decoupling to strong decoupling from 2004 to 2013 (Period III). Adjusting plantation structure, technology innovation and raising awareness of water-saving, may promote the decoupling degree between WF and agricultural GDP in Beijing.